2004
DOI: 10.1271/bbb.68.1525
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Benzoquinone by Yeast Cells and Oxidative Characteristics of Corresponding Hydroquinone: Application to Highly Sensitive Measurement of Yeast Cell Density by Using Benzoquinone and a Chemiluminescent Probe

Abstract: The metabolic efficiency of seven derivatives of 1,4-benzoquinone (BQ) by yeast cells and the oxidative characteristics of the corresponding hydroquinones (HQs) were studied by electrochemical, spectrophotometric and chemiluminescent methods. The spectrophotometric method was based on the reduction of a tetrazolium salt to formazan dye during the autoxidation of HQs generated by yeast cells under alkaline conditions. The amounts of HQs detected directly by the electrochemical method did not agree with those ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Such a hypothesis was proved by the experimental facts that the substantial generation of hydrogen peroxide was observed in the procedure of TS metabolism in the cytosol and S9 fractions using NADPH as the cofactor, and the addition of UDPGA completely inhibited the hydrogen peroxide generation. The quinone reduction and subsequent autoxidation, which was known as the quinone redox cycle, had been widely observed for many other quinones [33,34].…”
Section: Discussionmentioning
confidence: 96%
“…Such a hypothesis was proved by the experimental facts that the substantial generation of hydrogen peroxide was observed in the procedure of TS metabolism in the cytosol and S9 fractions using NADPH as the cofactor, and the addition of UDPGA completely inhibited the hydrogen peroxide generation. The quinone reduction and subsequent autoxidation, which was known as the quinone redox cycle, had been widely observed for many other quinones [33,34].…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism of the autoxidation of PCB derived hydroquinone may be similar to 1,4-hydroquinone because of their similar thermodynamic and kinetic properties. (shown in Eq 3An induction period has been reported in the studies on the autoxidation process of some hydroquinone family members(14,43,64). James et al(61) reported that various methyl-substituted 1,4-hydroquinones autoxidize after an induction period.…”
mentioning
confidence: 90%